Тенденция к оптимальной организации системы видовых пара- дигм в русском языке - Vladimir Klimonov (Studia Rossica Posnaniensia)
The reorganization of the initial system of aspect paradigms in Old Russian is investigated within the framework of the theory of natural grammar. It is claimed, in accordance with this theory, that the grammatical changes in morphological systems of natural languages are determined by a limited set of typologically relevant markedness principles (naturalness principles or preference laws). These principles explain the attested diachrony of grammatical changes in the system of aspectual paradigms of the Russian verb and predict the general direction in its development. During the historical development of the system of aspectual paradigms in Russian, optimal iconic perfectivizing paradigms are ousting non-optimal countericonic imperfectivizing paradigms as well as non-optimal non-iconic aspectual syncretic paradigms. In contemporary Russian, aspectual paradigms of perfectivization are preferable in terms of competitive aspectual paradigms of imperfectivization and syncretic aspectual paradigms. The share of optimal paradigms of perfectivization is constantly increasing in modern Russian. Consequently, there is direct evidence for the development of the system of Russian aspect paradigms towards optimal organization of aspect paradigms, i.e. towards economy.